The Newest Technology of Psychotherapy with Participants of Military Conflict - Ostrovska, Kateryna; Sulyatytskyy, Ivan; Ostrovskii, Igor (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
The article presents a new proven psychotherapeutic technology, created by the method of combination of Psychology of Possibilities, Solution Focused Brief Therapy and concepts of Integration Methodology.Psychotraumas, especially Post-Traumatic Stress Disorders, which received by the victims of military conflicts, are often so individualized, that require multistage and multidirectional psychological help approaches. Release from persecution and memories of the past as a reminders of the trauma and creating perspective for further life through rethinking the experience are the main goal of psychotherapy.That`s the two most vulnerable categories of modern military conflict in eastern Ukraine, which are participants in the Joint Forces Operation (under JFO) and Inwardly Displaced Persons (under – IDP) from the zone of JFO. Psychotherapeutic practice with them encourages us to create a new technological model of psychological care to this category of clients. Its essence is integrated use of three different conceptual therapeutic technologies, which is Solution Focused Brief Therapy, concepts Psychology of Possibilities and concepts of Integration Methodology. Optimally invest in the person's attitude that everyone has a large reserve for further self-realization (attitude not on oneself, not on problems, but exclusively on the resource of personal future) and bring a person to a functional state are the main goal of all technology. If this is achieved, the need to look for flaws automatically disappears, and even more there will be no need to delve into the client's past. This is the newest approach to restoring mental health, increase resistance (immunity) to traumatic effects creation of support for virtually all three psychotherapeutic concepts presented by us through various holistically oriented psychological techniques and algorithms.As a result of passing the offered complex psychotherapy general improvement of the psychological condition of the categories of clients affected by the war in the East creates empirical arguments of validity as a new technology of integrated approach in providing psychological care in particular in work with psychotraumas at participants of military conflict for actualization in them of a resource of personal growth.
Keywords: free imagination; maevtic dialogue; concepts of Integration Methodology; concepts Psychology of Possibilities, Solution Focused Brief Therapy; personal resource; client`s acceptance; psychotraumas